Concentration of rhenium from dilute sodium chloride solutions - DRAGOLJUB M. LUKIC; JURIJ L. VUCINA; SLOBODAN K. MILONJIC (Journal of the Serbian Chemical Society, 2008)
The conditions for the desorption of rhenium from the anion exchange resin Dowex 1-x8 by HNO3, HCl, H2SO4 and NaOH were determined. The solution (5.0´10-3 mol dm-3 Re in 0.15 mol dm-3 NaCl) was passed through a column containing 0.10 g of the resin. The total sorbed amount of rhenium was 0.20 g/g of the resin. It was then eluted by the corresponding eluent in the concentration range up to about 3.0 mol dm-3. The highest elution efficiency and the most favourable elution profile were found with 3.0 mol dm-3 HNO3. Over 77 % of the sorbed rhenium was found in the first 5 ml of the eluate. Practically all the rhenium was recovered with 20 ml of the acid. Under the given experimental conditions, HCl and H2SO4 were less favourable while NaOH was not applicable, due to very low efficiency of rhenium elution.